Revisualizing Visual Culture - Bailey, Chris; Gardiner, Hazel (Farnham Ashgate, 2010)
n the past twenty years digital technology has had a radical impact on all the disciplines associated with the visual arts - this book provides expert views of that impact. By looking at the advanced ICT methods now being employed, this volume details the long-lasting effects and advances now made possible in art history and its associated disciplines. The authors analyze the most advanced and significant tools and technologies, from the ongoing development of the Semantic Web to 3D visualization, focusing on the study of art in the various contexts of cultural heritage collections, digital repositories and archives. They also evaluate the impact of advanced ICT methods from technical, methodological and philosophical perspectives, projecting supported theories for the future of scholarship in this field. The book not only charts the developments that have taken place until now but also indicates which advanced methods promise most for the future.Contents: Preface; Introduction: making knowledge visual, Chris Bailey; Do a thousand words paint a picture?, Mike Pringle; The semantic web approach to improving access to cultural heritage, Kirk Martinez and Leif Isaksen; Resource discovery and curation of complex and interactive digital datasets, Stuart Jeffrey; Digital exploration of past design concepts in architecture, Daniela Sirbu; Words as keys to the image bank, Doireann Wallace; For one and all: participation and exchange in the archive, Sue Breakell; The user-archivist and collective (in)voluntary memory: read/writing the networked digital archive, James McDevitt; Internet art history 2.0, Charlotte Frost; Museum migration in century 2.08, Jemima Rellie; Slitting open the Kantian eye, Charlie Gere; Bibliography; Index.About the Editor: Chris Bailey is Professor of Cultural History and Dean of the Faculty of Arts and Society at Leeds Metropolitan University. Hazel Gardiner is Editor for the Corpus of Romanesque Sculpture in Britain and Ireland and joint-editor of the CHArt (the Computers and the History of Art) Yearbook. She was Senior Project Officer for the AHRC ICT Methods Network.Reviews: 'Exploring in book format the impact of information and communication technologies on the disciplines of art history and visual culture might seem incongruous at first. Yet it is precisely the pause between technological advance and epistemological catch-up - and the nature of these adjustments - that this lively and engaging publication asks us to consider. The essays cover from multiple perspectives some key issues facing historians of art and visual culture in the 21st century: from scholars who have observed the impact of ICT on their fields in recent years, to younger writers of the digital generation who have known nothing else. From the electronic structures that comprise and deliver digital images and associated data, to the shifting relations between custodians, curators and the widened constituencies with which they now engage, the impact of ICT is one that has far-ranging ramifications on the formation of knowledge and the practices of visual culture research. This book will play an important role in provoking thought about these issues'. Catherine Moriarty, Brighton University, UK 'Revisualizing Visual Culture is recommended for information professionals who are currently navigating the challenges of arts and humanities analysis and display.' Online Information Review